The Psychology of BNPL Repayment Procrastination: Behavioral Insights on Present Bias and Financial Motivation - Lie, Marisa; Sahda Putra, Bani; Sammuel Sulu, Jimmy; Tanjung, Miranda (Journal The Winners, 2025)
This study aims to examine BNPL repayment procrastination through the lens of Temporal Motivation Theory (TMT), particularly focusing on three key components, namely present bias, value, and delay (installment period). To achieve the study aim, survey data were collected from 134 active BNPL users in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The obtained results showed that present bias significantly increased BNPL repayment procrastination, while perceived value (reward) did not directly reduce it. Furthermore, delay (installment period) was found to positively contribute to procrastination but did not moderate the relationship between present bias and procrastination. The insignificant moderating effects of value and delay suggest that long-term BNPL users may not prioritize rewards when postponing repayments. The results also show that financially stable users with fixed incomes and short-term installment preferences have less tendency to procrastinate, while those with high outstanding balances or longer installment plans face greater risks. This study extends the application of TMT in a fintech context and provides practical insights for improving BNPL risk assessments, designing repayment schemes, and promoting financial literacy. As a recommendation, future investigation should explore factors such as self-control, financial literacy, and perceived financial stress to gain deeper insights into BNPL repayment behavior across diverse consumer segments.